2020
DOI: 10.3389/fncel.2020.593305
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage Increases Level of Heme Oxygenase-1 and Biliverdin Reductase in the Choroid Plexus

Abstract: Subarachnoid hemorrhage is a specific, life-threatening form of hemorrhagic stroke linked to high morbidity and mortality. It has been found that the choroid plexus of the brain ventricles forming the blood-cerebrospinal fluid barrier plays an important role in subarachnoid hemorrhage pathophysiology. Heme oxygenase-1 and biliverdin reductase are two of the key enzymes of the hemoglobin degradation cascade. Therefore, the aim of present study was to investigate changes in protein levels of heme oxygenase-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Cerebral vasospasm is an important complication of SAH, and the two important candidates for causing cerebral arterial spasm are the red blood cell product HbO 2 and the vasoconstrictor ET. Some scholars have found [15] that the combination of HbO 2 and ET activates diffusion neurons in the cerebral cortex in vivo, and suggests the nitric oxide scavenging function of HbO 2 . When the availability of nitric oxide decreases, the threshold concentration of ET induced cerebral ischemia significantly decreases through the complex interaction between the neuronal astrocyte network In general, astrocyte damage in SAH patients was positively correlated with the content of ACKR3, Cx43, HbO 2 , and ET in cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral vasospasm is an important complication of SAH, and the two important candidates for causing cerebral arterial spasm are the red blood cell product HbO 2 and the vasoconstrictor ET. Some scholars have found [15] that the combination of HbO 2 and ET activates diffusion neurons in the cerebral cortex in vivo, and suggests the nitric oxide scavenging function of HbO 2 . When the availability of nitric oxide decreases, the threshold concentration of ET induced cerebral ischemia significantly decreases through the complex interaction between the neuronal astrocyte network In general, astrocyte damage in SAH patients was positively correlated with the content of ACKR3, Cx43, HbO 2 , and ET in cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Previous studies have revealed that inflammation can disrupt the integrity of ChP barriers, leading to the accumulation of immune cells. [57][58][59] In this study, we employed ZO-1, a classical tight junction protein, as an indicator of blood-CSF barrier integrity in PHH. The results revealed a disrupted ZO-1 staining pattern in the choroid plexus of PHH.…”
Section: Tsos Inhibited the Occurrence And Progression Of Hydrocephal...mentioning
confidence: 99%